Reversible phase transformation phenomenon in titanium dioxide films: Evidence beyond interface-nucleation and dissolution-precipitation kinetics. (March 2018) - Gautam, Subodh K.; Singh, Jitendra; Shukla, D.K.; Pippel, E.; Poddar, P.; Singh, Fouran
Abstract: The re-crystallization kinetics and rutile to anatase reversible phase transformation (PT) in nano-crystalline titanium dioxide (TiO2 ) are reported. Initially, an amorphous TiO2 film is used for the present study and in situ isothermal annealing dependent nucleation and growth kinetics of anatase and rutile phase is studied at low temperature (∼523 K) and well explained using Johnson–Mehl–Avrami-Kolmogorov (JMAK) model. The anatase nanocrystallite (NCs) transformation into rutile phase is reported with isothermal annealing for longer time and temperature dependent annealing in lower temperature range 523 K–673 K and explained using interface-nucleation mechanism. Furthermore, the thermodynamic stability of rutile NCs and lattice stress-induced reversible PT in nano-sized rutile TiO2 are confirmed in moderate temperature range (623 K - 973 K) and well explained using x-ray diffraction, micro-Raman spectroscopy and near edge x-ray absorption fine structure spectroscopy studies. However, annealing at higher temperature (1123 K - 1323 K) induces the growth of anatase NCs and their natural transform into rutile phase are explained by well-known dissolution–precipitation mechanism. Activation energy of rutile PT is quantified and found higher for dissolution-precipitation mechanism than that for interface nucleation at earlier stage. Thus, overall PT kinetics at different temperature range is well understood by invoking in three step mechanism: I) early stage anatase-to-rutile transformation is dominated by interface-nucleation, II) then intermediate stage reversible rutile-to-anatase PT and, III) at later stages, anatase-to-rutile PT is controlled by dissolution–precipitation mechanism. Graphical abstract: Image 1